THE PROTECTION OF EMPLOYEES AT WORK - Jovanović, Predrag P; Božičić, Darko M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Question of employee’s protection at work has a vital significance for labour relations. When it comes to employee’s protection at work it is not just about protection of physical integrity but also moral integrity. This is because not only manpower, as an organic unity of health and work abilities takes part in labour relations, but also the entire personality of employee with the overall personal integrity, which also on its part requires appropriate labour law treatment and protection. Any kind of injury at work or professional illness cause the negative economic and social consequences for both, employee (because only a healthy employee can work and earn for a living) and employer as well (because this situation leads to decrease in profit). Taking into account importance which employee’s protection at work has for labour relations, it is not surprising that international and european labour law abound with legislation in this area. That is why substantial part of this paper is dedicated to international and european labour law standards about employee’s protection at work.